New Zealand's Meat Board, Markets and the Killing Season: A Twentieth-Century Labour History of Unintended Consequences. (1st May 2018) - Curtis, Bruce
Abstract : From its beginnings (in 1923), the New Zealand Meat Producers' Board, a statutory agency representing the collective interests of farmers, unintentionally and indirectly empowered meatworkers and their unions. This empowerment was instituted despite farmers and the Board being inherently hostile towards labour organisation. Through the Board, farmers exercised a self-interested collective control in local and international product markets that also benefited meatworkers in localised labour markets. The Board used its statutory powers to limit the scale and scope of meat companies and, by limiting their powers in the product markets of central concern to farmers, made these companies commensurately weak in labour markets. This analysis owes much to the insights of Fligstein and Fernandez (1988) regarding weak employers. Farmers' unintended empowerment of meatworkers as militant unionists was a remarkable irony given the often bitter antagonism between the two groups over industrial relations in New Zealand.